Factors contributing towards excellence academic performance - Yahaya, Azizi (2008)
In the just release results of the STPM (Sijil Tinggi Pelajaran Malaysia) and the SPM (Sijil Pelajaran Malaysia) for the year 2003 respectively, only about 1% of students were top performers. The media also reported various comments from top performing students themselves on how they have managed so very well in these public examinations. Coincidently, their comments are very much consistent with what the experts have put forth like the roles of teachers and schools, peers, family, and students themselves are important contribution towards achieving top academic results.